sa_AFLP_458ind_335char - Gussarova, Galina; Allen, Geraldine A.; Mikhaylova, Yulia; McCormick, Laurie J.; Mirré, Virginia; Marr, Kendrick L.; Hebda, Richard J.; Brochmann, Christian (Dryad Digital Repository, 2015)
AFLP data matrix (0;1). See description in the readMe file.